The 1:2 co-crystal formed between N,N′-bis(pyridin-4-ylmethyl)ethanediamide and benzoic acid: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
The crystal and molecular structures of the title 1:2 co-crystal, C14H14N4O2-2C7H6O2, are described. The oxalamide molecule has a (+)-antiperiplanar conformation with the 4-pyridyl residues lying to either side of the central, almost planar C2N2O2 chromophore (r.m.s. deviation = 0.0555 A˚ ). The benzoic acid molecules have equivalent, close to planar conformations [C6/CO2 dihedral angle = 6.33 (14) and 3.43 (10)]. The formation of hydroxy-O—HN(pyridyl) hydrogen bonds between the benzoic acid molecules and the pyridyl residues of the diamide leads to a three-molecule aggregate. Centrosymmetrically related aggregates assemble into a six-molecule aggregate via amide-N—HO(amide) hydrogen bonds through a 10-membered {HNC2O}2 synthon. These are linked into a supramolecular tape via amide-N—HO(carbonyl) hydrogen bonds and 22-membered {HOCONC4NH}2 synthons. The contacts between tapes to consolidate the three-dimensional architecture are of the type methylene-C—HO(amide) and pyridyl-C—HO(carbonyl). These interactions are largely electrostatic in nature. Additional non-covalent contacts are identified from an analysis of the calculated Hirshfeld surfaces.